A conservation trade-off? Interspecific differences in seahorse responses to experimental changes in fishing effort - Curtis, Janelle M. R. (2016)
1. A 2-year experimental seining programme and underwater visual censuses were undertaken to quantify the direct effects of active demersal fishing on the population structure and relative abundance of two sympatric seahorse species of conservation concern: the European long-snouted seahorse, Hippocampus guttulatus Cuvier 1829 and the short-snouted seahorse, Hippocampus hippocampus L. The influence of habitat preference on population-level responses to changes in habitat structure following a reduction in fishing effort was also investigated. 2. It was predicted that the benthic habitat would be more structurally complex after fishing ceased and that seahorse densities would increase in response to reduced fishing mortality. Furthermore, it was predicted that the magnitude of the increase in density would be greater for H. guttulatus than for H. hippocampus, because the former species prefers complex vegetated habitats while the latter species uses sparsely vegetated habitats. 3. As predicted, the amount of habitat cover increased significantly when seining ceased, primarily through increases in the abundance of drifting macroalgae and unattached invertebrates. Despite similarities in life histories, the two seahorse species responded differently in terms of magnitude and direction to reduced fishing effort: the abundance of H. guttulatus increased significantly while H. hippocampus decreased in abundance. 4. Results suggest that active demersal fishing may influence the magnitude and direction of the responses of benthic marine fishes to exploitation through its impacts on habitat structure. An increase in habitat cover appeared to favour higher densities of H. guttulatus when seining effort was reduced. By contrast, repeated seining, which maintained less complex habitats, appeared to favour greater abundances of H. hippocampus. 5. Given differences in habitat preference among benthic marine fishes subject to incidental capture in fisheries, simultaneous attempts to manage populations of sympatric species may require complementary strategies that support the persistence of diverse habitat types. Copyright (c) 2006 John Wiley & Sons, Ltd.